Ecological Analysis of Stunted Toddler in Indonesia - Agung Dwi Laksono1 , Ina Kusrini2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The results of the Indonesia Basic Health Survey (Riskesdas) in 2007, 2013 and 2018 showed the stunted rate for toddlers was still above 30%. While proven poverty often comes with stunted on toddlers. The study aimed to answer whether poverty factors and the availability of health services are related to the prevalence of stunted toddlers in provinces in Indonesia. This study was a secondary data analysis “Data and Information: Indonesian Health Profile in 2017”. The results showed that the high percentage of the poor population (>14.43%) was dominated by the high prevalence of stunted toddlers (22.51%-30.0%). In the category of health center ratio per 100 thousand high population (?4) seen dominated by the prevalence of stunted toddlers in the high category (22.51%-0.0%). In the category of nutritionist ratio per 100 thousand high population (>12), it appears to be dominated by the prevalence of stunted toddler in the high category (22.51% -30.0%). In the category of midwife ratio per 100 thousand high population (>97) was dominated by the prevalence of stunted toddler (22.51%-30.0%). It was concluded that the percentage of the poor population was positively related to the prevalence of stunted toddler. While health service input factors (health center, nutritionists, and midwives) were not related to the prevalence of stunted toddlers.